PERAN KOMISI PEMILIHAN UMUM KABUPATEN KEPULAUAN MERANTI DALAM MENINGKATKAN PARTISIPASI MASYARAKAT KABUPATEN KEPULAUAN MERANTI PADA PEMILIHAN UMUMTAHUN 2014 - Ade Suprenda; Ikhsan Ikhsan; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One year after the holding of the 1999 elections, the government together with the DPR passed Law Number 4 of 2000 concerning amendments to Law Number 3 of 1999 Concerning Elections. The main content of Law Number 4 of 2000 is an important change, namely that the holding of elections is carried out by an institution called the General Election Commission (KPU) which is independent and nonpartisan. KPU has representatives in each region tasked with carrying out elections in the provinces, and districts / cities, namely the Provincial KPU, and the Regency / City KPU. In the Indonesian constitutional system, the duties, authority, and obligations of the KPU in organizing the elections are not only related to the parties participating in the election, but also involve public participation as voters in the election. There are still areas that have not yet reached the target number of voters set by the KPU of Kepulauan Meranti Regency, which is 75%. This shows the low level of community participation in elections in the Meranti Islands Regency. Evidenced by the many people who did not use their voting rights during the election. Based on the description from the background above, the writer is interested in studying more deeply about this issue with the title, "The Role of the Meranti Islands Regency Election Commission in Increasing the Participation of the People of the Meranti Islands Regency in the 2014 General Election". This type of research can be classified as empirical or sociological legal research, because in this study the writer directly conducts research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted at the Meranti Islands Regency KPU. Sources of data used, namely: primary data, secondary data and tertiary data. Data collection techniques in this research were Observation, Interview, and Literature Study. The conclusion that can be obtained from the results of the first research, The role of KPU in increasing public participation in the presidential election and legislative election is to socialize to the voters regarding the presidential and legislative elections. This role was considered successful because according to data the community participation rate which was originally in 2009 amounted to 63.00% now in 2014 rose to 82.40%. Second, the obstacles encountered by the Meranti Regency KPU in increasing voter participation in the 2014 presidential election and legislative election include the distance traveled which is still considered an obstacle. Then regarding the mindset of people who are still indifferent to the democratic party, namely the presidential election and the legislative election, each has their own reasons why they did not participate. And next about the DPT, a classic problem that never ends. Keywords: Role-Commission Election-Community Participation